Risk factors for diabetic foot ulcers mortality and novel negative pressure combined with platelet-rich plasma therapy in the treatment of diabetic foot ulcers - Wang, Yanling; Liu, Bang; Pi, Yinzhen; Hu, Li; Yuan, Yeling; Luo, Jiao; Tao, Yixiao; Li, Ping; Lu, Shan; Song, Wei (Frontiers in Pharmacology, 2022)
The purpose of this study was to assess the risk factors for morbidity and mortality of diabetic foot ulcers (DFUs). For the treatment of diabetic foot ulcers, negative pressure wound therapy (NPWT) combined with platelet-rich plasma-fibrin glue (PRP) was also investigated. There were 653 patients in the diabetic foot ulcer group and 510 patients in the diabetic patients without foot ulceration (NFU) group, for a total of 1163 patients in the study samples after individuals without follow-up were excluded. The patients were randomized into two groups: the negative pressure wound therapy group and the negative pressure wound therapy combined with the PRP group. The findings of the univariate analysis revealed the blood indicators for predicting diabetic foot ulcer morbidity risk factors, such as C-reactive protein, albumin, creatinine, alkaline phosphatase, procalcitonin, platelets, 25-hydroxyvitamin D, β-2-microglobulin, monocyte ratio, low-density protein cholesterol (LDL), triglyceride, alanine aminotransferase (ALT), aminotransferase (AST), creatine kinase (CK) and total cholesterol. Using logistic regression analysis revealed only albumin and age to be independent predictors of diabetic foot ulcer mortality. Our study also revealed that, compared to negative pressure wound therapy alone, negative pressure wound therapy combined with PRP accelerated wound healing and reduced the mortality rate. According to the findings of this pilot study, new risk factors for diabetic foot ulcer morbidity and mortality have been found, and negative pressure wound therapy combined with PRP therapy may provide the first information that it is an effective adjunct treatment for diabetic foot ulcers.